2002
DOI: 10.1126/science.1071220
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of Synaptonemal Complex Length and Mammalian Meiotic Exchange Rates

Abstract: Analysis of recombination between loci (linkage analysis) has been a cornerstone of human genetic research, enabling investigators to localize and, ultimately, identify genetic loci. However, despite these efforts little is known about patterns of meiotic exchange in human germ cells or the mechanisms that control these patterns. Using recently developed immunofluorescence methodology to examine exchanges in human spermatocytes, we have identified remarkable variation in the rate of recombination within and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
248
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(280 citation statements)
references
References 17 publications
24
248
1
1
Order By: Relevance
“…35 The average number of recombinatorial events per cell in control males has been shown to be approximately 50 through cytogenetic studies and immunofluorescence data. 36,[38][39][40][41][42] There is a significant degree of variability between controls (13-25%) and between cells from the same individual (range: 42.5-55.3 recombination foci per cell). [39][40][41][42] The majority of published studies provide evidence of a significant reduction in recombination events per cell in NOA individuals compared to controls (40-42 versus 46-49).…”
Section: Meiotic Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The average number of recombinatorial events per cell in control males has been shown to be approximately 50 through cytogenetic studies and immunofluorescence data. 36,[38][39][40][41][42] There is a significant degree of variability between controls (13-25%) and between cells from the same individual (range: 42.5-55.3 recombination foci per cell). [39][40][41][42] The majority of published studies provide evidence of a significant reduction in recombination events per cell in NOA individuals compared to controls (40-42 versus 46-49).…”
Section: Meiotic Recombinationmentioning
confidence: 99%
“…36,[38][39][40][41][42] There is a significant degree of variability between controls (13-25%) and between cells from the same individual (range: 42.5-55.3 recombination foci per cell). [39][40][41][42] The majority of published studies provide evidence of a significant reduction in recombination events per cell in NOA individuals compared to controls (40-42 versus 46-49). 33,35,36 Two studies have reported no such difference in overall recombination between NOA and controls.…”
Section: Meiotic Recombinationmentioning
confidence: 99%
“…Greenwood, B. Rana, and N. Schork, in prep.). However, there is growing evidence that there exists very large variation in recombination rates among individuals during human meiosis (Cullen et al 2002;Lynn et al 2002). Because this individual variation is not really captured by simple specification of interlocus recombination fractions in genetic maps (which represent only "average" rates of recombination), it is an open question as to the degree to which such individual variation influences not only genetic map construction, but also the use of genetic maps in multipoint linkage analysis contexts.…”
Section: Genetic and Physical Mapsmentioning
confidence: 99%
“…The SC consists of two axial/lateral elements which contain Synaptonemal Complex Protein 2 (SCP2) and Synaptonemal Complex Protein 3 (SCP3) connected by transverse filaments which include Synaptonemal Complex Protein 1 (SCP1) (Fig. 6) [Vidal et al 1987;Lynn et al 2002;de Vries et al 2005;Ollinger et al 2005]. The complete SC resembles a ladder-like structure with SCP3 and SCP2 forming the legs and SCP1 forming the rungs.…”
Section: Synaptonemal Complexmentioning
confidence: 99%
“…The number of crossovers (measured as the number of MLH1 foci) in a spermatocyte or oocyte varies by sex [Lynn et al 2002]. Human males have an average of 50 crossover sites per spermatocyte while females have about 70 per oocyte .…”
Section: Introductionmentioning
confidence: 99%